Compact Two-Phase Immersion Cooling With Dielectric Fluid for PCB-Based Power Electronics - Aleksandar Ristic-Smith; Daniel J. Rogers (IEEE Open Journal of Power Electronics, 2024)
This paper explores two-phase immersion cooling using sealed enclosures of dielectric fluid as a technique to achieve compact, power dense converters on a single printed circuit board (PCB). The proposed approach employs passive circulation of the fluid and does not introduce system complexity beyond a heat exchanger required to condense the vapour. A test apparatus representing six 650 V, 150 A semiconductor switches in an inverter rejecting heat to a 65 $\,^{° }$ C water cooling loop is developed. Pool boiling experiments on a flat surface in Novec 7000 dielectric fluid demonstrate critical heat flux of 43 W cm $^{-2}$ at a saturation temperature of 94 $\,^{° }$ C and a corresponding pressure of 593 kPa. By augmenting the surface with pin fins (representative of a heat spreader attached to a switch) and grit blasting to improve the surface micro-geometry, the maximum heat transfer coefficient increased from 1.5 W cm $^{-2}$ K $^{-1}$ to 3.4 W cm $^{-2}$ K $^{-1}$ with a corresponding reduction in switch temperature from 125 $\,^{° }$ C to 107 $\,^{° }$ C at the total power dissipation of 186 W. A practical implementation with comparable thermal performance to the experimental apparatus but minimised volume of 0.12 L is presented. This yields a Cooling System Performance Index of 37 WL $^{-1}$ K $^{-1}$ , including the heat exchanger and printed circuit board with switches, decoupling capacitors and gate drivers.